1989
DOI: 10.1111/j.1346-8138.1989.tb01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Observations of Mosquito Bite Reactions in Man: A Survey of the Relationship between Age and Bite Reaction

Abstract: To evaluate the mechanism of mosquito bite reaction in man, the reaction to Aedes albopictus was observed in 162 subjects ranging in age between 1 to 68 years old. Bite reactions were found to consist of both an immediate and a delayed reaction. The eruption and time course of the immediate reaction were consistent with type I hypersensitivity. The eruption and time course of the delayed reaction were consistent with cutaneous basophil hypersensitivity. Positive rates of immediate reaction increased from early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 14 publications
6
30
0
1
Order By: Relevance
“…The skin reactions to mosquito bites are derived from salivary secretions and consist of an immediate and a delayed reaction [24, 25]. In the present study, 7 of the 12 subjects with immediate skin reactions to SGE of A. togoi using the skin prick test had significantly higher anti-mosquito IgE antibody levels than those without a skin reaction (fig.…”
Section: Discussionsupporting
confidence: 53%
“…The skin reactions to mosquito bites are derived from salivary secretions and consist of an immediate and a delayed reaction [24, 25]. In the present study, 7 of the 12 subjects with immediate skin reactions to SGE of A. togoi using the skin prick test had significantly higher anti-mosquito IgE antibody levels than those without a skin reaction (fig.…”
Section: Discussionsupporting
confidence: 53%
“…Two different types of responses in the cerebral cortex can be induced by stimulation of the non-specific thalamic nuclei, depending on the frequency of stimulation. Low frequency stimulation (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) produces slow waves and spindle bursts (recruiting responses) associated with inattention, drowsiness, and sleep, whereas high frequency stimulation ( > 50 Hz) is followed by desynchronization of electrocortical activity with concomitant arousal (Dempsey and Morison,'42;Morison and Dempsey,'42;Jasper,'49,'60;Moruzzi and Magoun,'49). The phenomenon of cortical recruiting will not be further discussed, since recent evidence suggests that the projections of other nuclei which have been included in the non-specific thalamus, such as the ventral medial and ventral anterior nuclei, are better candidates for the final pathway mediating this phenomenon (Starzl and Magoun,'51;Herkenham,'79,'86).…”
Section: F'unctional Considerationsmentioning
confidence: 99%
“…In vitro lymphocyte proliferation reactions were highest in subjects with delayed reactions, suggesting a type IV, delayed-type hypersensitivity (DTH) reaction (Peng and Simons 1996). Cutaneous basophil hypersensitivity has also been implicated in delayed reactions to mosquito bites (Oka and Ohtaki 1989). Lastly, a study examining 402 children aged 1 month to 18 years showed that mean levels of mosquito salivaspecific IgE and IgG declined with age after early childhood suggesting that natural desensitization may occur (Peng et al 2004).…”
Section: Mosquitoesmentioning
confidence: 96%